Rancang Bangun Sistem Komunikasi Bluetooth Low Energy (BLE) Pada Sistem Pengamatan Tekanan Darah - Arief Sukma Indrayana; Rakhmadhany Primananda; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Technology development can make human works easier in various fields, for example health field. One of the example technology application in health field is automatically blood pressure measurement. Technology that can do thing like that is Internet of Things. Internet of Things is a concept where physical object like refrigerators, lights, etc can communicate with each other through a protocol, such as Bluetooth Low Energy. Bluetooth Low Energy is a Classic Bluetooth development version that specifically implemented on Internet of Things. Bluetooth Low Energy has advantages over other protocols such as better power saving, wide connectivity range and fast data transmission. Therefore, researcher conducted research by implementing Bluetooth Low Energy in real life which is blood pressure measurement. The results of this study show that blood pressure monitoring works succesfully where the sensor can monitor the blood pressure automatically and the data results succesfully sent via Bluetooth Low Energy. In this research, Bluetooth Low Energy data transmission performance is tested with two scenarios, distance modification and connection interval modification. The average of delivery delay is 2.81 seconds and 2.6 seconds respectively. These test scenarios show that distance & connection interval can affect the Bluetooth Low Energy performance